Identification of QTLs for growth period traits in soybean using association analysis and linkage mapping. Issue 3 (15th April 2013) - Zuo, Qiaomei; Hou, Jinfeng; Zhou, Bin; Wen, Zixiang; Zhang, Shuyun; Gai, Junyi; Xing, Han; Morris, B.
Abstract The growth period traits of soybean (Glycine max L. Merr.) are quantitatively inherited and crucial for its adaptation to different environments. Association analysis and linkage mapping were used to identify the quantitative trait loci (QTLs) for days to flowering (DF), days from flowering to maturity (DFM) and days to maturity (DM). Considering the effect of sowing date, the phenotypes were evaluated in three or four sowing‐date‐experiments in each year. A total of 96 associations, involving 19 SSRs corresponding to DF, DFM and/or DM, were identified by association mapping. Six, eight and two QTLs were observed relating to DF, DFM and DM by linkage mapping, respectively, and some QTLs were shared by DF, DFM and DM. Four SSRs (Satt150, Satt489, Satt172 and Sat_312) were found to be related to the growth period traits using the two mapping methods. In summary, association analysis and linkage mapping can complement and verify results from both methods to identify QTLs in soybean, and these findings may be useful in facilitating the selection of growth period–related traits via marker‐assisted selection.